MENINGKATKAN PEMBELAJARAN SEPAKBOLA DENGAN MENGGUNAKAN PERMAINAN SEPAKBOLA MINI PADA SISWA KELAS V SD INPRES ILIGETANG - MARIA NOO MAWA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The background of this research is the need for efforts to improve learning outcomes in soccer learning by using mini soccer games for fifth grade students of SD Inpres Iligetang. The problem in this research is: Can implementing mini soccer play improve soccer learning outcomes in fifth grade students of SD Inpres Iligetang? This study aims to improve soccer learning outcomes using mini soccer games for fifth grade students of SD Inpres Iligetang. The population taken was students in grade V of SD Inpres Iligetang, totaling 21 students. In the research, the variables are football and mini soccer games. To obtain suitable data, in this study using the Classroom Action Research (CAR) method. From the observations obtained with the help of the checklist, it can be seen that the percentage of psychomotor, cognitive, and affective aspects of the fifth grade students of Inpres Iligetangs elementary school has been given an increase in learning in cycle I and cycle II, the percentage increased from 23.50% to 80 , 95%. Thus the action of learning soccer by implementing mini soccer games on the fifth grade students of SD Inpres Iligetang can be said to be successful. And it is expected for Physical Education teachers in Elementary Schools to be able to apply mini soccer games to students in Physical Education, Sports and Health learning.